Controlled synthesis of graphitic carbon-encapsulated α-Fe2O3 nanocomposite via low-temperature catalytic graphitization of biomass and its lithium storage property. (1st January 2016) - Wu, Feng; Huang, Rong; Mu, Daobin; Wu, Borong; Chen, Yongjian
Graphical abstract: Highlights: Facile synthesis of graphitic carbon/α-Fe2 O3 nano-sized anode composite. In situ low temperature catalytic graphitization of biomass material. Onion-like graphitic carbon layers conformally encapsulating around α-Fe2 O3 core. High lithium storage properties, especially, outstanding cycle performance. Abstract: A delicate structure of graphitic carbon-encapsulated α-Fe2 O3 nanocomposite is in situ constructed via "Absorption–Catalytic graphitization–Oxidation" strategy, taking use of biomass matter of degreasing cotton as carbon precursor and solution reservoir. With the assistance of the catalytic graphitization effect of iron core, onion-like graphitic carbon (GC) shell is made directly from the biomass at low temperature (650 °C). The nanosized α-Fe2 O3 particles would effectively mitigate volumetric strain and shorten Li + transport path during charge/discharge process. The graphitic carbon shells may promote charge transfer and protect active particles from directly exposing to electrolyte to maintain interfacial stability. As a result, the as-prepared α-Fe2 O3 @GC composite displays an outstanding cycle performance with a reversible capacity of 1070 mA h g −1 after 430 cycles at 0.2C, as well as a good rate capability of ∼ 950 mA h g −1 after 100 cycles at 1C and ∼ 850 mA h g −1 even up to 200 cycles at a 2C rate.